2008
DOI: 10.1074/jbc.m804826200
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Cross-links Reveal Conserved Features of DNA Topoisomerase I Architecture and a Role for the N Terminus in Clamp Closure

Abstract: In eukaryotes, DNA topoisomerase I (Top1) catalyzes the relaxation of supercoiled DNA by a conserved mechanism of transient DNA strand breakage, rotation, and religation. The unusual architecture of the monomeric human enzyme comprises a conserved protein clamp, which is tightly wrapped about duplex DNA, and an extended coiled-coil linker domain that appropriately positions the C-terminal active site tyrosine domain against the Top1 core to form the catalytic pocket. A structurally undefined N-terminal domain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…In contrast, when the shorter human linker was inserted into the yeast enzyme (in (hL)-yTop1) and expressed in yeast, the cells were viable and relatively resistant to CPT. In this case, our findings are consistent with a defect in DNA binding, suggested by earlier studies of related yTop1 clamp constructs (20).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In contrast, when the shorter human linker was inserted into the yeast enzyme (in (hL)-yTop1) and expressed in yeast, the cells were viable and relatively resistant to CPT. In this case, our findings are consistent with a defect in DNA binding, suggested by earlier studies of related yTop1 clamp constructs (20).…”
Section: Discussionsupporting
confidence: 81%
“…We previously demonstrated that locking the human Top1 clamp around the DNA prevents strand rotation within the Top1-DNA intermediate (19). Similar impediments to DNA rotation were observed with the analogous studies of yeast Top1 (20), suggesting a conservation of protein clamp enzyme architecture and catalytic mechanism.…”
mentioning
confidence: 53%
See 3 more Smart Citations